Resources, society, and the future : a report - Bertelman, Tomas, 1945- (Pergamon international library of science, technology, engineering, and social studies., 1980)
Resources, Society and the Future is a report on resources and raw materials and their implications for the future of the Swedish society. This report aims to create a framework for a continuous dialogue in Sweden between the general public and their political representatives, the scientific world and interest groups of all kinds. Two debates in Sweden are considered, one of them centering on national interests, that is, Sweden's needs for industrial production and exports, and the other concerning long-term questions of human survival (environment, resource base, and questions of equity betwe.